A chromosomal investigation of some European species of Haliplidae (Coleoptera) - Powell, Joseph E.; Angus, Robert B. (Memorie della Società Entomologica Italiana, 2006)
The karyotypes of 15 European species of Haliplidae are described and illustrated. The sex chromosomes are X0 in Brychius elevatus and Peltodytes caesus, and XY in 13 species of Haliplus. The number of autosome pairs is 16 in Peltodytes caesus, 19 in Brychius elevatus, 17 in Haliplus (Liaphlus) fulvus, 15 in H. (L.) variegatus, 14 in H. (L.) flavicollis, 11 in H. (L.) laminatus, 9 in H. (L.) mucronatus, and 11 in H. (Haliplidius) obliquus and H. (H.) confinis, H. (Neohaliplus) lineatocollis and five species of H. (Haliplus). It is suggested that the X0 sex chromosome system, the most common in the Adephaga, is plesiotypic for Haliplidae, and that the XY systems are a synapomorphy of the family, and are neo-XY in origin. There is no good evidence of Xyp systems of the type found in Polyphaga. The diversity of karyotypes shown by species of the subgenus Liaphlus is contrasted with the near uniformity shown by other groups. Interspecific differences between karyotypes are noted.